The Impact of the COVID-19 Pandemic on the Mental Health of Healthcare Workers in Italy: Analyzing the Role of Individual and Workplace-Level Factors in the Reopening Phase After Lockdown - Moro, Maria Francesca; Calamandrei, Gemma; Poli, Ranieri; Di Mattei, Valentina; Perra, Alessandra; Kurotschka, Peter Konstantin; Restrepo, Alexandra; Romano, Ferdinando; La Torre, Giuseppe; Preti, Emanuele; Mascayano, Franco; Picardi, Angelo; et al. (Frontiers in Psychiatry, 2022)
Introduction: Italy is one of the high-income countries hit hardest by Covid-19. During the first months of the pandemic, Italian healthcare workers were praised by media and the public for their efforts to face the emergency, although with limited knowledge and resources. However, healthcare workers soon had to face new challenges at a time when the national health system was working hard to recover. This study focuses on this difficult period to assess the impact of the COVID-19 pandemic on the mental health of Italian healthcare workers. Materials and methods: Healthcare workers from all Italian regions [n = 5,502] completed an online questionnaire during the reopening phase after the first wave lockdown. We assessed a set of individual-level factors (e.g., stigma and violence against HCWs) and a set of workplace-level factors (e.g., trust in the workplace capacity to handle COVID-19) that were especially relevant in this context. The primary outcomes assessed were score ≥15 on the Patient Health Questionnaire-9 and score ≥4 on the General Health Questionnaire-12, indicators of clinically significant depressive symptoms and psychological distress, respectively. Logistic regression analyses were performed on depressive symptoms and psychological distress for each individual- and workplace-level factor adjusting for gender, age, and profession. Results. Clinically significant depressive symptoms were observed in 7.5% and psychological distress in 37.9% of HCWs. 30.5% of healthcare workers reported having felt stigmatized or discriminated, while 5.7% reported having experienced violence. Feeling stigmatized or discriminated and experiencing violence due to being a healthcare worker were strongly associated with clinically significant depressive symptoms [OR 2.98, 95%CI 2.36-3.77 and OR 4.72 95%CI 3.41-6.54] and psychological distress [OR 2.30, 95%CI 2.01-2.64 and OR 2.85 95%CI 2.16-3.75]. Numerous workplace-level factors, e.g., trust in the workplace capacity to handle COVID-19 [OR 2.43, 95%CI 1.92-3.07] and close contact with a co-worker who died of COVID-19 [OR 2.05, 95%CI 1.56-2.70] were also associated with clinically significant depressive symptoms. Similar results were found for psychological distress. Conclusions. Our study emphasizes the need to address discrimination and violence against healthcare professionals and improve healthcare work environments to strengthen the national health systems’ capacity to manage future emergencies.